External validation of a simple risk score based on the ASPRE trial algorithm for preterm pre‐eclampsia considering maternal characteristics in nulliparous pregnant women: a multicentre retrospective cohort study. (29th April 2020) - Brunelli, E; Seidenari, A; Germano, C; Prefumo, F; Cavoretto, P; Di Martino, D; Masturzo, B; Morano, D; Rizzo, N; Farina, A
Abstract : Objective: To validate the performance of a first‐trimester simple risk score based on the ASPRE trial algorithm for pre‐eclampsia. Design: Multicentre retrospective cohort analysis. Setting: Four Italian hospitals. Population: Unselected nulliparous women at 11–13 weeks of gestation from January 2014 through to January 2018. Methods: Model performance was evaluated based on discrimination and calibration. Main outcome measures: Delivery before 37 weeks of gestation with a diagnosis of pre‐eclampsia. Results: Based on 73 preterm pre‐eclampsia cases and 7546 controls (including 101 cases of late pre‐eclampsia), the area under the receiver operating characteristics curve was 0.659 (95% CI 0.579–0.726). The sensitivity was 32.9% (95% CI 22.1–43.7) at a false‐positive rate of 8.8%. The positive likelihood ratio was 3.74 (95% CI 2.67–5.23), the positive predictive value was 3.49% (95% CI 2.12–4.86%) and the negative predictive value was 99.3% (95% CI 99.1–99.5%). The sensitivity and positive likelihood ratio were approximately 40% lower than in the original study. The calibration analysis showed a good agreement between observed and expected risks ( P  = 0.037). Comparison with the Fetal Medicine Foundation (FMF) algorithm yielded a difference in the area under the curve of 0.084 ( P  = 0.007). Conclusions: In our Italian population, the simple risk score had a lower performance than expected for the prediction of preterm pre‐eclampsia in nulliparous women. The FMF algorithm applied to the same data set resulted in a better prediction. Tweetable abstract: Simple risk score predicts preterm pre‐eclampsia in Italy. Tweetable abstract: Simple risk score predicts preterm pre‐eclampsia in Italy.